PENGARUH SISTEM PERTANAMAN KAKAO TERHADAP INTENSITAS SERANGAN PENYAKIT VSD (Vascular streak dieback) PADA KEBUN KAKAO RAKYAT DI KECAMATAN BUNGKU TENGAH - As’ar, Marwia; Shahabuddin, Shahabuddin; Lakani, Irwan (AGROTEKBIS, 2018)
This aim of the study was to determine the cropping systems of small holder cocoa plantations on the intensity of VSD (Vascular streak dieback) attacks. This study would be useful information for farmers on how to control VSD attacks on cocoa plantation particularly in Central Bungku. The research used descriptive methods. Data collected in this study was done through survey on two types of cacao plantations i.e. polyculture system and monoculture system. It was found that the attacks of the VSD disease were more intense in the monoculture system than its counterpart. The intensity of the VSD attack was 2.58% in the monoculture system whereas it was only 1.48% in the polyculture system.